A role for fibronectin-leucine-rich transmembrane cell-surface proteins in homotypic cell adhesion - Karaulanov, Emil E (2006)
The fibronectin-leucine-rich transmembrane (FLRT) family of leucine-rich repeat (LRR) proteins is implicated in fibroblast growth factor (FGF) signalling, early embryonic development and neurite outgrowth. Here, we have analysed whether FLRTs may also function in cell adhesion. We find that FLRT proteins can physically interact and that FLRT-transfected cultured cells sort out from non-transfected cells, suggesting a change in adhesive properties. A similar sorting effect is also observed in Xenopus embryos and tissue aggregates. FLRT-mediated cell sorting is calcium dependent and substrate independent. Deletion analysis indicates that cell sorting requires the LRR domains, which are dispensable for FLRT-mediated FGF signalling. Conversely, sorting is independent of the cytoplasmic domain, which is essential for FLRT-induced signalling. Therefore, FLRT-mediated FGF signal transduction and homotypic cell sorting can be molecularly uncoupled. The results indicate that FLRT proteins have a dual role, promoting FGF signalling and modulating homotypic cell adhesion.